Penelitian Antiimplantasi Ekstrak Etanol Daging Buah Burahol (Stelechocarpus burahol Hook F. & Thomson) Pada Tikus Putih - Sunardi, Clara; Sumiwi, Sri Adi; Hertati, Ai (UI Scholars Hub, 2010)
We examined antiimplantation effect of ethanol extract from ripening burahol flesh (Stelechocarpus burahol Hook f. & Thomson) using doses 1g and 0.5g per Kg Body Weight (BW) on White Female Rats Wistar Strain. The ethanol extract was given orally on daily basis from diestrus phase until 7th day of pregnancy. Two parameter used in this investigation were number of implants and number of born fetus. The fetus were examined by observing their morphology to identify the existence of teratogenic effect. The result showed that the two doses reduced both the number of implants and born fetus significantly. In addition, the burahol flesh as an antifertility agent has two functions: as antiimplantation and abortifacient. Lastly morphological examination on the fetus did not show any teratogenic effect.